Post Hoc Assessment of Time to Clinical Response Among Adults Hospitalized with Community-Acquired Bacterial Pneumonia Who Received Either Lefamulin or Moxifloxacin in 2 Phase III Randomized, Double-Blind, Double-Dummy Clinical Trials. (24th April 2020) - Lodise, Thomas; Colman, Sam; Stein, Daniel S; Fitts, David; Goldberg, Lisa; Alexander, Elizabeth; Scoble, Patrick J; Schranz, Jennifer
Abstract: Time to clinical response, a proxy for hospital "discharge readiness, " was compared between CABP inpatients who received lefamulin or moxifloxacin in the Lefamulin Evaluation Against Pneumonia (LEAP) trials. The analysis included 926 inpatients. A short and comparable median time to clinical response (4 days) was observed in both treatment groups.